Implementation of 5s in HRM - Uma, Dr. D.S.; Kannan, Aadharsh (Journal of Contemporary Research in Management (JCRM), 2013)
Everything changes, and changes constantly: technologies, competitors, customers, suppliers, employees, the economy, the overall business environment—everything. To stay competitive, a company has to respond. And since an organization is a living, interconnected, and integrated system, an action taken in one place influences things elsewhere. A good 5S training program sensitizes people to all kinds of ways they can become more productive. The five S’s are seiri (putting things in order); seiton (arranging things efficiently), seiso (preventing problems by keeping things clean); seiketsu (doing after-work maintenance and cleanup), and shitsuke (showing discipline, following the rules). Anytime it takes people more than a few seconds to find something, they will ask themselves why. A Five S program is usually a part of, and the key component of establishing a Visual Workplace, and are both a part of Kaizen — a system of continual improvement. This paper discusses the implementation of 5S concept in Human resource management.